ChemInform Abstract: A Three‐Component Reaction Between 1‐Substituted‐2‐methylimidazoles, Cyanophenylacetylene, and Various Aldehydes: Stereoselective Synthesis of (Z)‐(2‐Cyano‐1‐phenyl)vinyl Ethers of 2‐(2‐Hydroxyalkyl)imidazoles. Issue 52 (24th December 2013) - Trofimov, Boris A.; Andriyankova, Ludmila V.; Nikitina, Lina P.; Belyaeva, Kseniya V.; Mal'kina, Anastasiya G.; Afonin, Andrei V.; Ushakov, Igor' A.
Abstract A novel functionalization of imidazoles (I) at the C2‐methyl is achieved through a three‐component reaction with aliphatic and aromatic aldehydes and cyanophenylacetylene without a catalyst.